1993
DOI: 10.1002/j.1460-2075.1993.tb05998.x
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination-dependent initiation of DNA replication from DNA damage-inducible origins in Escherichia coli.

Abstract: Escherichia coli cells induced for the SOS response express inducible stable DNA replication (iSDR) as an SOS function. Initiation of iSDR is independent of transcription, translation and DnaA protein, which are essential for initiation of DNA replication from oriC. We found that a recA mutant that is defective in recombination but proficient in SOS induction could not elicit iSDR. In contrast, iSDR was enhanced by recD and recJ mutations that inactivate the exonuclease V activity of the RecBCD enzyme and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 76 publications
2
76
0
Order By: Relevance
“…Thus, the initiation mechanisms of these replication systems are most likely to share common features. iSDR induction in recD and recBC sbcA mutant cells requires an SOS-inducing treatment (Asai et al, 1993), although the nuclease activity of RecBCD is absent in these mutants. In this study we have shown that, when DSBs are artificially provided in these mutant cells, RDR is initiated without SOS-inducing treatments.…”
Section: Isdr As a Special Type Of Dsb-triggered Rdrmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, the initiation mechanisms of these replication systems are most likely to share common features. iSDR induction in recD and recBC sbcA mutant cells requires an SOS-inducing treatment (Asai et al, 1993), although the nuclease activity of RecBCD is absent in these mutants. In this study we have shown that, when DSBs are artificially provided in these mutant cells, RDR is initiated without SOS-inducing treatments.…”
Section: Isdr As a Special Type Of Dsb-triggered Rdrmentioning
confidence: 97%
“…Extraction of total DNA and Southern blot hybridization were carried out as described previously (Magee et al, 1992;Asai et al, 1993). The BamHI fragment (1.7 kb) of pHK carrying the kanamycin gene was used to prepare 32 P-labeled probe for detection of pHK and its derivatives.…”
Section: Assay For Origin-independent Plasmld Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not eliminate the possibility of chromosomal hotspots for recombinationdependent adaptive mutation that occurs using a mechanism very similar to that used on the F'. Good candidates for such sites are the terminus of replication, which is a RecBCD-dependent recombination hotspot (Louarn et aL, 1991), and the oriM sites at which RecBC-dependent 'stable' DNA replication is initiated (Asai et aL, 1993); there may well also be others that are exclusive to starvation conditions, and others which have not yet been considered. This question will be resolved only when an Findependent site is found that undergoes Rec-dependent adaptive mutation similar to that described for the F', or when the search for such sites has been exhausted.…”
Section: A Role For Conjugation?mentioning
confidence: 99%
“…So far, three categories of proteins that participate in BIR have been identified: recombination proteins, replication proteins, and proteins mediating recombination and replication (mediator proteins). Recombination proteins, including RecA in E. coli, uvsX in bacteriophage T4, and RAD52, RAD51, RAD54, RAD55, and RAD57 in S. cerevisiae, initiate BIR by promoting strand invasion and Dloop formation (Lark et al 1978;Formosa and Alberts 1986a,b;Asai et al 1993;Davis and Symington 2004;Malkova et al 2005). The role of mediator proteins is to assemble a processive replication fork on the D-loop that is formed during the first step of BIR.…”
mentioning
confidence: 99%